The Relationship Between Farmer Competence and Shallot Farm Income (Allium Ascalonicum L.) - Aisyah, Siti; Faqih, Achmad; Putra, Anak Agung; Rahayu, Siti Rahma; Ma’aniyatun, Ma’aniyatun; Yahya, Reza Taufiq (Green Publisher Indonesia, 2023)
One of the causes of low productivity of a crop is that farmers have not fully applied production technology. One of the efforts made to increase onion production is through the adoption of innovation and new technology. The purpose of this study was to determine the relationship between knowledge competence, attitudes and skills of farmers with shallot (Allium ascalonicum L.) farming income. The study will be conducted from January to April 2023. The method used in this study is a descriptive quantitative research method with survey research techniques. The respondents in this study were 55 shallot farmers in Sidamulya Village, Jalaksana District, Kuningan Regency. Data analysis techniques in this study use correlational analysis to measure the relationship of variables / sub-variables to other variables. The results showed that there was a moderate and real relationship between farmers' knowledge and shallot farm income, with a value of rs = 0.560 and tarithmetic value is 5.060. There is a moderate and real relationship between farmers' attitudes and shallot farm income, with a value of rs = 0.544 and a calculated value of 4.850. There is a moderate and real relationship between farmers' skills and shallot farm income, with a value of rs = 0.550 and tarithmetic value is 4.927.